Immunocytochemical verification of the insulin receptor's specificity in the nuclear envelope of Tetrahymena. Comparison with receptors of the plasma membrane. Issue 1 (February 1994) - Csaba, G.; Hegyesi, Hargita
Abstract : The unicellular Tetrahymena possess hormone receptors in the nuclear envelope similarly to higher rank animals. These receptors bind insulin and their specificity is detectable by monoclonal antibodies developed to insulin. The hormonal (insulin) pretreatment (imprinting) of the cell did not alter the binding capacity of the nuclear membrane, demonstrated by antibody-technique. The specific binding characteristics of the plasma membrane was demonstrated and this was significantly increased following imprinting. In the nucleus of Tetrahymena presence of insulin was not detected by immunocytochemical method.